A general nonexistence result for inhomogeneous semilinear wave equations with double damping and potential terms. (March 2021) - Jleli, Mohamed; Samet, Bessem; Vetro, Calogero
Abstract: We investigate the large-time behavior of solutions for a class of inhomogeneous semilinear wave equations involving double damping and potential terms. Namely, we first establish a general criterium for the absence of global weak solutions. Next, some special cases of potential and inhomogeneous terms are studied. In particular, when the inhomogeneous term depends only on the variable space, the Fujita critical exponent and the second critical exponent in the sense of Lee and Ni are derived.